Efeito de formigas parabióticas Crematogaster levior Longino, 2003 e Camponotus femoratus (Fabricius, 1804) sobre a herbivoria em plantas de clareiras amazônicas - Silva, Camila Benedita da (2017)
The herbivory in tropical forests mainly occurs in expanding leaves, rich in nitrogen and water, and lacking chemical defenses and a quite common adaptation for the biotic defense of these plants are the extrafloral nectars (NEFs). Interactions involving NEFs are facultative and conditional, but a highly specialized mutualistic interaction between ants and plants are the ant gardens. Ants' gardens (JFs) are a sophisticated association of epiphytic plants with two species of parabiotic ants (Crematogaster levior and Camponotus femoratus), which are extremely aggressive, occurring primarily in natural clearings or in riparian vegetation. This study investigated the effect of parabiotic ants on herbivores and herbivory on JFs clearing plants. The hypothesis is that antler gardens sheltering plants have less herbivores and lower rates of herbivory compared to those in which gardens are absent. In two areas of Amazon forest in Cláudia (Mato Grosso, Brazil), 33 clearings were sampled along pre-existing tracks (16 with JFs and 17 without JFs). In each clearing, the proportion of leaf area removed was obtained in plants with extrafloral nectary (n = 20) and without extrafloral nectary (n = 20). There were no differences in the average percentage of herbivory observed in plants without extrafloral nectary with the presence (12% of herbivory) or absence (11% of herbivory) of JFs. For plants with extrafloral nectary (NEF), this percentage was lower in the presence of JFs (5%) than in their absence (7%). The herbivorous insects registered in the plants are distributed in four orders: Coleoptera (n = 117), Lepidoptera (n = 87), Hemiptera (n = 77) and Orthoptera (n = 54). The average herbivore per clearing was 10 individuals, minimum of three and maximum of 21 herbivores. Parabolic ants can extend their role as defense of the plants of the gardens to those that develop in the same clearing, particularly with the presence of extrafloral nectaries. However, there was no decrease in the number of herbivores in parabiotic ant clearings, nor was there a change in the composition of herbivores as to the presence or absence of JFs.